2018
DOI: 10.3389/fgene.2018.00048
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation of the Endangered Neotropical Catfish Steindachneridion scriptum (Siluriformes: Pimelodidae)

Abstract: Steindachneridion scriptum is an important species as a resource for fisheries and aquaculture; it is currently threatened and has a reduced occurrence in South America. The damming of rivers, overfishing, and contamination of freshwater environments are the main impacts on the maintenance of this species. We accessed the genetic diversity and structure of S. scriptum using the DNA barcode and control region (D-loop) sequences of 43 individuals from the Upper Uruguay River Basin (UUR) and 10 sequences from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Previous reports yielded 33 haplotypes and 149 polymorphic sites in 83 specimens from four extant Pacifastacus species (Larson et al 2016); 36 haplotypes and 56 variable sites in 43 sequences of Steindachneridion scriptum (Paixão et al 2018); and, 44 haplotypes and 76 variable sites in 74 fish (Pappalardo et al 2015). In this study, the genetic variability (Hd = 0.999) is similar, but nucleotide diversity (Pi = 0.73721) is higher than the ones (Hd = 0.959; Pi = 0.007) reported by Paixão et al (2018) from Steindachneridion scriptum; and in 68 species of Sicyopus zosterophorum (Hd = 0.885; Pi = 0.0039) by Taillebois et al (2013). It has been reported that Tajima's D-neutrality tests are applied to detect evidence of strong selective pressures, while Fu's Fs-tests are used specifically to identify population expansion (Tajima 1989;Fu 1997) D* = 2.17427, P < 0.02; Fu and Li's F* 1.7450, p < 0.005) for all individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports yielded 33 haplotypes and 149 polymorphic sites in 83 specimens from four extant Pacifastacus species (Larson et al 2016); 36 haplotypes and 56 variable sites in 43 sequences of Steindachneridion scriptum (Paixão et al 2018); and, 44 haplotypes and 76 variable sites in 74 fish (Pappalardo et al 2015). In this study, the genetic variability (Hd = 0.999) is similar, but nucleotide diversity (Pi = 0.73721) is higher than the ones (Hd = 0.959; Pi = 0.007) reported by Paixão et al (2018) from Steindachneridion scriptum; and in 68 species of Sicyopus zosterophorum (Hd = 0.885; Pi = 0.0039) by Taillebois et al (2013). It has been reported that Tajima's D-neutrality tests are applied to detect evidence of strong selective pressures, while Fu's Fs-tests are used specifically to identify population expansion (Tajima 1989;Fu 1997) D* = 2.17427, P < 0.02; Fu and Li's F* 1.7450, p < 0.005) for all individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Following the stream hierarchy model (SHM) [78], obligate freshwater fish populations are often genetically structured and differentiated (freshwater fish, mean Fst = 0.222) [79] at both among and within river basin scales as the results of gene-flow restriction and dispersal limitation among populations [80][81][82][83][84]. Isolation by distance (IBD) [85], isolation by barriers (IBB) (e.g., dams, culvert, waterfalls, rapids) [86], and isolation by resistance (IBR) (e.g., temperature, stream gradient, number of confluences, drainage basin, seasonal precipitation, seasonal water flow, and high flow events) [87,88] are reported to influence genetic variation in riverine freshwater fishes [89].…”
Section: Phylogeography and Population Structurementioning
confidence: 99%
“…To date, computational methods and NGS have been employed by conservation and evolutionary geneticists to improve conservation management of marine populations, especially for endangered species. [46][47][48] Despite the technological advancements, analyzing genome-wide molecular data poses a major challenge. Handling large-scale and complex data requires high competency in bioinformatics and the ability to analyze and interpret the vast amount of data and translate them into biological applications.…”
Section: Current Challenges and Future Perspectivesmentioning
confidence: 99%